The volume and dynamics of international migration and transnational social spaces - Faist, Thomas, 1959- (Oxford : Clarendon, 2000)
This text analyses the causes, nature, and extent of the movement of migrants between affluent and poorer countries. It also examines the adaptation of immigrants to their surroundings and asks why many uphold ties to their places of origin.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Emigration and immigration